Sequencing Analysis of the ATOH7 Gene in Individuals with Optic Nerve Hypoplasia - Lim, Sing-Hui (2013)
PURPOSE: The Atonal Homolog 7 (ATOH7) gene has been implicated in association studies with optic nerve head diameter size. Hence, we screened optic nerve hypoplasia (ONH) patient DNA samples from Australia, France, and the United States for sequence variants in the ATOH7 gene using Sanger sequencing. METHODS: Sanger sequencing of the ATOH7 gene was performed on 34 affected individual DNA samples. Sequencing was also carried out in 3 unaffected family members to confirm segregation of identified single nucleotide variations. RESULTS: Seven sequence variations were identified in ATOH7. No disease-causing sequence changes in the ATOH7 gene was discovered in the ONH patient samples. CONCLUSIONS: Mutations within the ATOH7 gene are not implicated in the pathogenesis of optic nerve hypoplasia in our patient cohort.